Sensemaking in Bimbapedia's Marketing Communication Strategy in the Era of Digital Disruption via Instagram - Satria, Bagas; Liliyana, Liliyana; Alif, M. Ismail; Windratno, Haryo; Syatir, Syatir (Global Komunika : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the marketing communication strategy implemented by Bimbapedia through Instagram social media in facing competition in the era of digital disruption. This study uses a descriptive qualitative approach with in-depth interview techniques with three key informants: institution owners, social media admins, and digital marketing staff. Data analysis was carried out using the NVivo application with a thematic coding approach based on Karl E. Weick's sensemaking theory. The results of the study show that Bimbapedia's communication strategy is built through a sensemaking process involving seven main characteristics: identity-based meaning, reflection of past experiences, creation of a meaningful digital environment, social collaboration, continuous content updates, interpretation of audience cues, and feasibility-based decision making. Instagram is used not only as a promotional medium but also as a space for interaction and construction of meaning with the audience. This study concludes that the success of a digital marketing strategy in the era of disruption depends not only on the presence of technology but also on the organization's ability to interpret and respond to digital dynamics adaptively and with value.